Primal vision of the Sagada Igorots in the Mountain province of the Philippines : a thesis on the history of sacrifice - Kiley, Henry Wilson, 1936-
The specific peoples studied in this thesis are the inhabitants in and around the town of Sagada in the Mountain Province of the Philippines. This would include the peoples of Sagada proper and of the six villages located in a southerly direction from Sagada which is the municipal center. There are other villages which are part of the municipality of Sagada and which are excluded by this delimitation. These other villages have distinguishing linguistic characteristics which have affinities with those found outside of the municipality. This gives the reason for their exclusion. The point is that the political divisions in the Mountain Province of the Philippines do not correspond to the sociological, ethnic and linguistic groupings.
Submitted in partial fulfillment of the requirements for the degree of Master of Sacred Theology in the General Theological Seminary, New York City
Thesis (M. Theo.)-General Theological Seminary
Keywords: Igorot people -- Religion; Sacrifice